PENGARUH KINERJA KEUANGAN DAN INFLASI TERHADAP HARGA SAHAM PERUSAHAAN SUBSEKTOR FARMASI 2019-2023 - Maulana, Yasir; Agustin, Afni Alifia; Djuniardi, Dede (LPPM Universitas Banten jaya, 2026)
This research examines how internal financial conditions and inflation influence the stock prices of pharmaceutical sub-sector firms listed on the Indonesia Stock Exchange over the 2019–2023 period. Financial performance is represented by liquidity (Current Ratio/CR), leverage (Debt to Asset Ratio/DAR), and profitability (Return on Equity/ROE), while inflation is included as an external macroeconomic variable. The study applies a quantitative methodology with multiple linear regression as the main analytical tool. Secondary data are collected from corporate financial reports and publications issued by the Central Statistics Agency. The empirical results indicate that liquidity, leverage, profitability, and inflation jointly influence stock price movements. When examined individually, profitability shows a positive relationship with stock prices, whereas liquidity, leverage, and inflation exhibit negative but statistically insignificant effects. Overall, the findings suggest that sound financial performance combined with a stable macroeconomic environment contributes to strengthening investor confidence and shaping stock price dynamics in pharmaceutical sub-sector companies.